Health-related quality of life in rare gorms of childhood-onset hereditary spastic paraplegia - Schmidt, Henri; Battaglia, Nicole; Rong, Joshua; Tam, Amy; Carty, Siofra; Quiroz, Vicente; Yang, Kathryn; Zaman, Zainab; Schierbaum, Luca; Bernardi, Katerina; Alecu, Julian E.; Ebrahimi-Fakhari, Darius (Annals of Clinical and Translational Neurology, 2026)
We assessed health-related quality of life (HRQoL) in 80 children with rare hereditary spastic paraplegias using the Caregiver Priorities and Child Health Index of Life with Disabilities and clinician-reported outcomes. HRQoL was consistently reduced, particularly in relation to motor, autonomic, and bulbar symptoms. Children with complex HSP phenotypes had lower scores than those with pure forms. Scores correlated with established clinical scales but declined with age only in HSP-SPG11 and HSP-ZFYVE26. These findings identify key determinants of reduced quality of life and highlight clinical targets for supportive interventions in childhood-onset hereditary spastic paraplegia. Trial Registration: Registry and Natural History Study for Early Onset Hereditary Spastic Paraplegia: NCT04712812
Online veröffentlicht: 11. November 2025, Artikelversion: 11. Oktober 2025
Gesehen am 09.02.2026